Altruism and climate - Ingela Alger; Jörgen W. Weibull (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
Recognizing that individualism, or weak family ties, may be favorable to economic development, we ask how family ties interact with climate to determine individual behavior and whether there is reason to believe that the strength of family ties evolves differently in different climates. For this purpose, we develop a simple model of the interaction between two individuals who are more or less altruistic towards each other. Each individual exerts effort to produce a consumption good under uncertainty. Outputs are observed and each individual chooses how much, if any, of his or her output to share with the other. We analyze how the equilibrium outcome depends on altruism and climate for ex ante identical individuals. We also consider (a) coerced altruism, that is, situations where a social norm dictates how output be shared, (b) the effects of insurance markets, and (c) the role of institutional quality. The evolutionary robustness of altruism is analyzed and we study how this depends on climate.
Keywords: D02; D13; 330; altruism; family ties; individualism; moral hazard; evolution; Altruismus; Moral Hazard; Trittbrettfahrerverhalten; Theorie